Time-cost trade-offs in resource-constraint project scheduling problems with overlapping modes. (22nd October 2014) - Berthaut, François; Pellerin, Robert; Perrier, Nathalie; Hajji, Adnène
In companies, overlapping is commonly regarded as a promising strategy to accelerate project execution. Overlapping consists in executing in parallel two sequential activities by allowing a downstream activity to start before the end of an upstream activity based on preliminary information. However, overlapping can entail reworks in downstream activity, caused by information updates until finalised information is available, and additional coordination and communication, which both require additional time and costs. In this paper, we present a model for the resource-constrained project scheduling problem with feasible overlapping modes. The makespan minimisation and the gain maximisation problems are formulated as linear integer programmes. Time-cost tradeoffs between project duration and overlapping costs are also discussed. An example of a 30-activity project is provided to illustrate the utility and efficiency of the model. Our results highlight the closed interaction between resource constraints and overlapping modes and suggest the relevance of jointly considering them.